Social Media-Driven Routes to Positive Mental Health Among Youth: Qualitative Enquiry and Concept Mapping Study - Janhavi Ajit Vaingankar; Rob M van Dam; Ellaisha Samari; Sherilyn Chang; Esmond Seow; Yi Chian Chua; Nan Luo; Swapna Verma; Mythily Subramaniam (JMIR Publications, 2022)
BackgroundSocial media influence almost every aspect of our lives by facilitating instant many-to-many communication and self-expression. Recent research suggests strong negative and positive impacts of social media exposure on youth mental health; however, there has been more emphasis on harmful relationships. ObjectiveGiven the limited research on the benefits of social media for mental health, this qualitative study explored the lived experiences of youth to understand how social media use can contribute to positive mental health among youth. MethodsUsing an interpretivist epistemological approach, 25 semistructured interviews and 11 focus group discussions were conducted with male and female youth of different ethnicities (aged 15 to 24 years) residing in Singapore, who were recruited through purposive sampling from the community. We conducted inductive thematic analysis and concept mapping to address the research aims. ResultsWe found that youth engaged in a wide range of activities on social media from connecting with family and friends to participating in global movements, and these served as avenues for building positive mental health. Based on participants' narratives, our analysis suggested that positive mental health among youth could be influenced by 3 features of social media consumption (connection with friends and their global community, engagement with social media content, and the value of social media as an outlet for expression). Through these, pathways leading to the following 5 positive mental health components were identified: (1) positive relationships and social capital, (2) self-concept, (3) coping, (4) happiness, and (5) other relevant aspects of mental health (for example, positivity and personal growth). ConclusionsThe study results highlight the integral role of social media in the lives of today's youth and indicate that they can offer opportunities for positive influence, personal expression, and social support, thus contributing to positive mental health among youth. The findings of our research can be applied to optimize engagement with youth through social media and enhance the digital modes of mental health promotion.